Contribution for a double ephemeral: Carlos iii and his colonizing work on the presses. A state of affairs - Gómez Navarro, Soledad (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
The joint anniversaries of Charles III’s birth (200 years) and of his colonizing plan (250 years) seem to be opportune moments to stop, review and examine the production generated by academia on the latter, which has received noticeably less attention, the aim being to take stock of what we know, of what is lacking, of progress and of future challenges. Shining new light gained recently at different events commemorating the anniversary, this paper is set forth in two parts: (a) analyzing the compartments and contents of the different accumulated contributions – the sources and contents, authorships, chronologies and themes; (b) reflecting upon the profile of the panorama that is drawn in general and in certain concrete aspects.